P07.04 New molecular point-of-care test improves timeliness of treatment for chlamydia trachomatis (ct) and neisseria gonorrhoea (ng) in a remote aboriginal health clinic. (13th September 2015) - Huang, R; Ward, J; Tangey, A; Causer, L; Guy, R
Abstract : Introduction: High CT and NG prevalences have been observed in remote Aboriginal communities for decades. Testing and treatment are key prevention strategies, yet considerable delays in treatment occur, due to distances from laboratories and difficulties recalling patients. The TTANGO (Test, Treat ANd GO) randomised controlled trial is the first to evaluate whether a new point-of-care CT/NG test (GeneXpert) can improve the timelines of treatment and reduce re-infections rates in remote Aboriginal communities. Methods: In the context of TTANGO, we conducted an interim analysis to compare timelines of treatment before and after the point-of-care test was introduced at one of the 12 TTANGO sites. This site is one of seven remote clinics managed by Nganampa Health Council (NHC), an Aboriginal health service in South Australia. Results: Overall, 777 people were tested for CT/NG, 81 (10.4%) were positive; highest in 15–19 year olds (15.4%). In the point-of-care period, 40/40 (100%, 95% CI: 91.1–100) of people with a positive CT/NG point-of-care test received treatment, and of these 90% were treated in 24 h, with a median time-to-treatment of 0 days. In the standard-care period, 40/41 (97.6%, 95% CI: 87.1–99.9) received treatment; 15 (37.5%) were treated presumptively on the same day (due to symptoms/risk) and 25 (62.5%) were treated on the basis of the laboratory test result; and of these 44% were treated in 1–7 days, 44% in 8–14 days and 12% in 15+ days, with a median time-to-treatment of 8 days. Conclusion: This site is already part of a strong and comprehensive STI control program run by NHC over 20 years. Early findings from TTANGO show further improvement in STI management were achieved with point-of-care tests, with treatment occurring on average 8 days sooner for those treated on the basis of a test result. Future analyses will include all 12 clinics and also assess if re-infections have reduced. Disclosure of interest statement: No pharmaceutical grants were received in the development of this study. TTANGO is funded by a NHMRC project grant. The GeneXpert cartridges were purchased from Cepheid and Cepheid provided machines on loan for the duration of the study.